Effects of Basketball-specific High-intensity Interval Training on the Aerobic Capacity in Adolescent Female Basketball Players - DEAK, Graţiela-Flavia; OLARIU, Patrick; BOTA, Vlad-Călin; POP, Alexandra-Cristina; SZABÓ, Péter-Zsolt; KYRYCHENKO, Viktoriia; PĂTRAȘCU, Adrian (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2025)
Introduction: Basketball-specific high-intensity interval training (HIIT) has been documented to be a time-efficient, skill focused training method for enhancing the aerobic performance. The aim of this study was to investigate the effects of basketball-specific HIIT on aerobic capacity in adolescent female basketball players. Materials and methods: Participants were 16 female basketball players, aged 13-15 years. They were equally and randomly divided into two groups: a control group and an experimental group. The subjects from the experimental group performed a basketball-specific HIIT protocol for 6 weeks (2 times per week, 25 minutes per session), before the basketball training. The control group followed a basketball training program for the same period, with the same frequency (2 times a week, 90 minutes per session). Pre- and post-intervention, the multi-stage fitness (beep) test was used to assess aerobic endurance. Results: After 12 training sessions, the experimental group showed a significant increase in test scores (p = .002, with a mean difference of 1.263). When compared to the control group, post-intervention, the experimental group showed significantly higher test scores (p < .001, with a mean difference of 1.69). The findings suggest that aerobic endurance increases in adolescent basketball athletes after 6 weeks of training. Conclusion: Basketball-specific HIIT appears to be a solid option for improving aerobic performance in adolescent female players while maintaining focus on basketball skills. Article history: Received 2024 January 07; Revised 2025 January 20; Accepted 2025 January 22; Available online 2025.02.10; Available print 2025.02.28